ChemInform Abstract: 2‐Arylindoles: A New Entry to Transition Metal‐Free Synthesis of 2‐Aminobenzophenones. Issue 42 (September 2016) - Yu, Jin; Moon, Hye Ran; Min, Beom Kyu; Kim, Jae Nyoung
Abstract: Aminobenzophenones (II) and aminoaryl alkyl ketones (IV) are synthesized starting from substituted indoles under O2 balloon atmosphere without the need of transition metal catalysts or organometallic reagents.